2022
DOI: 10.1155/2022/5055338
|View full text |Cite|
|
Sign up to set email alerts
|

Economic Operation of the Regional Integrated Energy System Based on Particle Swarm Optimization

Abstract: Aiming at the problems of single planning technology and relatively few resource types in the process of regional comprehensive energy system planning at the current stage, this paper proposes a method based on the construction of regional comprehensive energy system planning and the operation model. Through the integration of the particle swarm optimization algorithm, this method can better realize the optimization and economic operation of the regional comprehensive energy system and build a system optimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Where t denotes the wide variety of particle iterations, vij denotes the speed of the ith particle in the jth dimension, and xij denotes the function of the ith particle in the jth dimension. c1 can decide the diploma of inheritance of the particle to its individual particle gold standard position, and c2 determines the diploma of inheritance of the particle to the world's most reliable particle function [14]. pij is the character intense value, which will be up to date in accordance with the historic ultimate cost for the duration of the particle iteration.…”
Section: Process and Topology Of Particle Swarm Optimization Algorithmmentioning
confidence: 99%
“…Where t denotes the wide variety of particle iterations, vij denotes the speed of the ith particle in the jth dimension, and xij denotes the function of the ith particle in the jth dimension. c1 can decide the diploma of inheritance of the particle to its individual particle gold standard position, and c2 determines the diploma of inheritance of the particle to the world's most reliable particle function [14]. pij is the character intense value, which will be up to date in accordance with the historic ultimate cost for the duration of the particle iteration.…”
Section: Process and Topology Of Particle Swarm Optimization Algorithmmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%